Mid‐infrared Fiber Optics for 1 — 18 μm Range. Issue 4 (December 2014) - Artyushenko, Viacheslav; Bocharnikov, Alexey; Sakharova, Tatiana; Usenov, Iskander
Abstract Development of infrared (IR) fibers and hollow waveguides (HWGs) was in good progress to meet growing market demands for laser power delivery, flexible IR‐imaging and remote process‐spectroscopy in spectral range from 1 to 18 μm. Parameters of IR‐glass fibers, polycrystalline IR‐fibers (PIR‐fibers) from silver halides and HWGs are compared to enable optimal choice for the production of IR‐cables, spectroscopy probes and multispectral bundles (Fig. 1).